Learning Approach for Enhancing Students' Creativity - Nilna Inayatan Nafiah; Alia Damayanti; Amalia Novita Putri Winarno; Diana Resti Akmalia; Febriana Nurdaningrum; Firzanah Arifatul Azizah; Illona Juditha; Ines Sandika Widya; Mutia Nur Afnia; Rizky Martiningrum (PT Ahan Group Publisher, 2025)
Creativity is an ability that students must have to face the challenges of the 21st century. In education, creativity is needed to help students understand abstract concepts, solve problems and create innovative ideas. This article aims to identify various effective learning approach strategies to stimulate students' creativity and create an inspiring and productive learning atmosphere. The Search, Appraisal, Synthesis and Analysis (SALSA) approach is used. The results show that several methods, such as mind mapping, Project-Based Learning (PjBL), critical thinking, and guided inquiry, positively impact student creativity. PjBL was considered the most effective of all the methods studied due to its holistic and contextual approach, providing meaningful and in-depth learning experiences. This study recommends the implementation of PjBL, supported by other strategies such as mind mapping, to create innovative learning relevant to students' needs.